Blunt Cardiac Injuries That Require Operative Management: A Single-Center 7-Year Experience - Seung Hwan Lee; Myung Jin Jang; Yang Bin Jeon (Journal of Trauma and Injury)
Purpose Blunt cardiac injuries (BCI) have a wide clinical spectrum, ranging from asymptomatic myocardial contusion to cardiac rupture and death. BCIs rarely require surgical intervention, but can be rapidly fatal, requiring prompt evaluation and surgical treatment in some cases. The aim of this study was to identify potential factors associated with in-hospital mortality after surgery in patients with BCI. Methods The medical records of 15 patients who had undergone emergency cardiac surgery for BCI between January 2014 and August 2020 were retrospectively reviewed. We included trauma patients older than 18 years admitted to Regional Trauma Center, Gachon University Gil Medical Center during the study period. Clinical and laboratory variables were compared between survivors and non-survivors. Results Non-survivors showed a significantly higher Injury Severity Score (p=0.001) and Abbreviated Injury Scale in the chest region (p=0.001) than survivors. American Association for the Surgery of Trauma-Organ Injury Scale Grade V injuries were significantly more common in non-survivors than in survivors (p=0.031). Non-survivors had significantly more preoperative packed red blood cell (PRBC) transfusions (p=0.019) and were significantly more likely to experience preoperative cardiac arrest (p=0.001) than survivors. Initial pH (p=0.010), lactate (p=0.026), and base excess (BE; p=0.026) levels showed significant differences between the two groups. Conclusions Initial pH, lactate, BE, ventricular injury, the amount of preoperative PRBC transfusions, and preoperative cardiac arrest were potential predictors of in-hospital mortality.